A Bridgman Furnace Front Tracking Model - Mooney, Robin Patrick (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2015)
The Bridgman furnace is widely used in industry and research, mainly because it provides a means to directionally solidify materials in a controlled manner, so that the resulting microstructure, and hence material properties, can be manipulated. This thesis details, firstly, the development and verification of a numerical Front Tracking Model (FTM) to track the position of, and growth conditions at, the columnar front during transient directional solidification in a Bridgman furnace; and, secondly, its application to experiments investigating Columnar to Equiaxed Transition (CET) in a gamma TiAl multicomponent hypoperitectic alloy. Previous FTMs have been applied in fixed grid numerical domains where the solidifying material - normally of hypoeutectic composition - is contained within that domain throughout simulations; the model demonstrated here accounts for movement of material through the domain and is adapted for hypoperitectic solidification. The model is applied, firstly, to characterise a Bridgman furnace in terms of heat transfer coefficients and, secondly, to simulate solidification conditions at, and ahead of, the growing columnar front during a unique set of experiments where Bridgman and power down modes of furnace operation are combined in series. The simulations carried out provide valuable insight, specifically, into the growth conditions that lead to CET in a multicomponent gamma TiAl alloy currently of interest to the aerospace industry; and, more generally, into the dynamics of the transient power down solidification process. The results from this work will be used in preparations for planned directional solidification experiments, using a similar gamma TiAl multicomponent alloy, on-board the European Space Agency MAXUS-9 sounding rocket (in microgravity) where a power down technique is employed. The model can be applied elsewhere, in industry and research, to provide insight into solidification conditions occurring in existing Bridgman processes and in the design of new furnaces.
PUBLISHED
Keywords: Bridgman furnace; solidification; numerical modelling; mechanical engineering; verification; characterisation; metallurgy; phase change; gamma titanium aluminide; power down; directional solidification; dendrite kinetics; columnar to equiaxed transition; Engineering, Ph.D.; Ph.D. Trinity College Dublin; Bridgman furnace; solidification; numerical modelling; mechanical engineering; verification; characterisation; metallurgy; phase change; gamma titanium aluminide; power down; directional solidification; dendrite kinetics; columnar to equiaxed transition; Nanoscience & materials; Heat transfer; Mechanical engineering; Metallurgy; Phase-change; Solidification; Transient and unsteady heat transfer; Front tracking; Numerical modelling; Verification